The Role of Tourism Infrastructure in Tourism Development: A Literature Review - Hesna, Yervi; Helmi, Helmi; Suraji, Akhmad; Lenggogeni, Sari (Journal of Infrastructure & Facility Asset Management, 2023)
Tourism is well-known as a profitable economic activities both to developed and developing countries. Many scholar has identified some benefit from tourism. Tourism can accelerate economic growth and regional development from tourist needs and activity in the destination. This research examines studies on tourism infrastructure that have been published in journals and other venues to develop better knowledge about the position of past and current research and to create recommendations for future research. After reviewing 27 publications, this research shows the importance of the infrastructure to support tourism development.